2020
DOI: 10.28982/josam.689130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D on mobilization, pulmonary function tests, grip strength and functionality in patients with spinal cord injury: A cross-sectional study

Abstract: How to cite/Atıf için: Koçak FA, Köseoğlu BF, Sütbeyaz ST. Impact of vitamin D on mobilization, pulmonary function tests, grip strength and functionality in patients with spinal cord injury: A cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that adequate levels of vitamin D are effective in the release of insulin from pancreatic beta cells [4]. The main form of circulating vitamin D is 25hydroxy (OH) vitamin D. The most important parameter that shows the amount of vitamin D in our body is 25 OH vitamin D [5]. Type 2 DM patients often have low 25 OH vitamin D levels, which could be associated with high fasting blood glucose (FBG) and glycated hemoglobin (HbA1c) levels [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that adequate levels of vitamin D are effective in the release of insulin from pancreatic beta cells [4]. The main form of circulating vitamin D is 25hydroxy (OH) vitamin D. The most important parameter that shows the amount of vitamin D in our body is 25 OH vitamin D [5]. Type 2 DM patients often have low 25 OH vitamin D levels, which could be associated with high fasting blood glucose (FBG) and glycated hemoglobin (HbA1c) levels [6].…”
Section: Introductionmentioning
confidence: 99%